2012
DOI: 10.1177/193229681200600517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insulin Feedback on Closed-Loop Glucose Control: A Crossover Study

Abstract: Addition of IFB to the PID controller markedly reduced the occurrence of hypoglycemia without increasing meal-related glucose excursions. Higher average BG levels may be attributable to differences in the determination of system gain (Kp) in this study. The prevention of postprandial hypoglycemia suggests that the PID + IFB algorithm may allow for lower target glucose selection and improved overall glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 13 publications
0
61
0
1
Order By: Relevance
“…Here, it is noted only that the use of glucagon does not ensure prevention of hypoglycemia and that repeated use might not be tolerated by all subjects. Generally, the hypoglycemic incidence rate with PID control has gone down as the meal response has improved, with studies by Weinzimer and coauthors 21,22 on the use of PID with insulin feedback (PID IFB ) and the use of PID IFB with or without pramlintide showing zero incidences in what are admittedly small studies.…”
Section: Review Of Available Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Here, it is noted only that the use of glucagon does not ensure prevention of hypoglycemia and that repeated use might not be tolerated by all subjects. Generally, the hypoglycemic incidence rate with PID control has gone down as the meal response has improved, with studies by Weinzimer and coauthors 21,22 on the use of PID with insulin feedback (PID IFB ) and the use of PID IFB with or without pramlintide showing zero incidences in what are admittedly small studies.…”
Section: Review Of Available Clinical Datamentioning
confidence: 99%
“…This is interesting insofar many investigators have concluded that meals cannot be controlled without open-loop bolus despite the fact that the initial 2006 PID study 2 did not include meal announcement and showed peak meal responses that were generally within 15-25 mg/dl of those observed in normal glucose-tolerant subjects who consumed the identical diet. 2 While Weinzimer coauthors 21,22 showed the peak response obtained with PID could be improved by giving one-third the normal meal bolus 15 min in advance of the meal, the reliance on meal boluses has steadily declined in subsequent PID studies. 4,5,6 The first report of PID IFB used only a small fixed bolus (2 U for all meals; Figure 3C).…”
Section: Review Of Available Clinical Datamentioning
confidence: 99%
“…The main aim is developing an artificial pancreas that has a low cost to be suitable for patients with type 1diabetes and artificial pancreas should be reliable with small size. There are many control techniques have been utilised for the artificial pancreas, such as PID control [20][21][22][23][24][25], adaptive control [26,27], model-predictive control [28], fuzzy logic control [29,30] and linear -quadratic Gaussian [25,31].…”
Section: Modelling An Artificial Pancreasmentioning
confidence: 99%
“…The glucose data were transmitted every minute via radiofrequency signaling. A laptop with the Control Tool software version 5.1, which uses Medtronic external Physiological Insulin Delivery (ePID) algorithm 5 with the Insulin Feedback (IFB) 10 feature, provided the automated insulin delivery during the CL phase and collected the glucose sensor data during the open-loop phase of the study. Although 2 Medtronic Sof-sensors were used, control of the CL software was set by the researcher to the sensor, which performed better and was switched to the other sensor as deemed necessary.…”
Section: Study Proceduresmentioning
confidence: 99%